Loud Noise Exposure Produces DNA, Neurotransmitter and Morphological Damage within Specific Brain Areas - Frenzilli, Giada; Ryskalin, Larisa; Ferrucci, Michela; Cantafora, Emanuela; Chelazzi, Silvia; Giorgi, Filippo S.; Lenzi, Paola; Scarcelli, Vittoria; Frati, Alessandro; Biagioni, Francesca; Gambardella, Stefano; Falleni, Alessandra; et al. (Frontiers in Neuroanatomy, 2017)
Exposure to loud noise is a major environmental thread to public health. Loud noise exposure, apart from affecting the inner ear, is deleterious for cardiovascular, endocrine and nervous systems and it is associated with neuropsychiatric disorders. In this study we investigated DNA, neurotransmitters and immune- histochemical alterations induced by exposure to loud noise in three major brain areas (cerebellum, hippocampus, striatum) of Wistar rats. Rats were exposed to loud noise (100 dBA) for 12 h. The effects of noise on DNA integrity in all three brain areas were evaluated by using Comet assay. In parallel studies, brain monoamine levels and morphology of nigrostriatal pathways, hippocampus and cerebellum were analyzed at different time intervals (24 h and 7 days) after noise exposure. Loud noise produced a sudden increase in DNA damage in all the brain areas under investigation. Monoamine levels detected at 7 days following exposure were differently affected depending on the specific brain area. Namely, striatal but not hippocampal dopamine significantly decreased, whereas hippocampal and cerebellar noradrenaline was significantly reduced. This is in line with pathological findings within striatum and hippocampus consisting of a decrease in striatal tyrosine hydroxylase combined with increased Bax and Glial Fibrillary Acidic Protein. Loud noise exposure lasting 12 h causes immediate DNA, and long-lasting neurotransmitter and immune-histochemical alterations within specific brain areas of the rat. These alterations may suggest an anatomical and functional link to explain the neurobiology of diseases which prevail in human subjects exposed to environmental noise.